Construction of Equality-Based Social Ethics in the Thoughts of Ibn Miskawaih and Al-Ghazali - Muhammad Hafidz Mahardika Arjuna; Chafid Wahyudi Chafid (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2026)
The degradation of contemporary social ethics has given rise to an urgent need for a normative foundation capable of addressing the phenomena of dehumanization, individualism, and social fragmentation. This article aims to reconstruct an equality-based social ethics through a synthesis of the concepts of justice (al-ʿadl) and interpersonal relations in the thought of Ibn Miskawaih and al-Ghazali. Regarding the provisional stance, this study assumes that the classical Islamic tradition of thought contains normative principles relevant to the renewal of social ethics, but the conceptual formulation of equality has not been systematically explored in previous studies, creating a research gap that needs to be filled. The study uses a qualitative philosophical-comparative approach based on library research. The analysis focuses on the construction of justice as an integral virtue and on the discourse of interpersonal relations (friendship, brotherhood, compassion, mutual assistance) as an arena for moral actualization. The findings indicate that justice in both thinkers functions as an ethical framework that unites various dimensions of social life; interpersonal relations become a concrete medium for moral expectations, and equality is understood as a recognition of the inherent moral dignity of each individual, rather than as equality of social status. The synthesis of these thoughts produces a conceptual model of equality-based social ethics that is relevant to addressing the ethical challenges of modern society and is expected to become a normative reference in the development of social policies and moral education practices.